Peran Masyarakat Dalam Menjaga Ketahanan Nasional Di Era Globalisasi - Eli Sabrifha (CV. SINAR HOWUHOWU, 2026)
National resilience is a nation’s ability to remain strong and resilient in the face of various obstacles and challenges, both domestic and international. In the current era of globalization, technological developments, the internet, and the influx of foreign cultures significantly impact people’s lives. Some of these influences are beneficial, while others can diminish love for one’s nation and state. Therefore, society plays a crucial role in maintaining national resilience and ensuring its strength and stability. This paper aims to explain the role of society in maintaining national resilience in the era of globalization. The method used is a literature review, drawing on information from books, journals, and other relevant sources. The results indicate that society can maintain national resilience by fostering a sense of nationalism, maintaining unity, using social media wisely, appreciating one’s own culture, and participating in national development. Furthermore, mutual respect and mutual cooperation are crucial for maintaining harmony amidst increasingly modern developments. Through cooperation between society and the government, national resilience can be maintained despite the various influences of globalization.